Answer:
The equation is
y = 2x/3 + 4/3
Step-by-step explanation:
The equation of a straight line is represented in the slope-intercept form, y = mx + c
Where c = y intercept
Slope, m = change in value of y on the vertical axis / change in value of x on the horizontal axis
change in the value of y = y2 - y1
Change in value of x = x2 -x1
y2 = final value of y
y 1 = initial value of y
x2 = final value of x
x1 = initial value of x
From the information given,
The points through which the line passed through are −1, −6 and , 5, −2
Slope, m = (y2-y1)/(x2-x1)
y2 = -2
y1 = -6
x2= 5
x1 = -1
Slope, m = (-2- -6)/(5- -1)
= 4/6 = 2/3
To find intercept, c
Let's use ( 5, −2)
-2 = 2/3 ×5 + c
-2 = 10/3 + c
c = -2 + 10/3 = 4/3
The slope-intercept equation will be
y = 2x/3 + 4/3